2009
DOI: 10.1056/nejmoa0803085
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Blood Pressure by Central Melanocortinergic Pathways

Abstract: Results of our genetic and pharmacologic studies implicate melanocortinergic signaling in the control of human blood pressure through an insulin-independent mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
364
2
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 426 publications
(401 citation statements)
references
References 28 publications
26
364
2
5
Order By: Relevance
“…Results obtained in binding studies supported present literature at human MCRs stating that NDP--MSH, -MSH and MT-II are non-selective agonists that bind to all MCRs, although -MSH had a relatively lower affinity for mouse MC1R compared to human (mouse IC 50 = 316  93 nM vs. human IC 50 = 5.97 nM) (Haskell-Luevano et al 1997). Furthermore, we found that neither MC1R, MC3R nor MC5R had a high affinity for LY2112688, whereas MC4R had a high affinity for LY2112688 supporting results found in human (Greenfield et al 2009). PG-901 is in the literature described as a human MC5R agonist, which also functions as an antagonist at human MC3R and MC4R (Grieco et al 2002), which correlates to results obtained on mouse MCRs.…”
Section: Binding Studiessupporting
confidence: 87%
“…Results obtained in binding studies supported present literature at human MCRs stating that NDP--MSH, -MSH and MT-II are non-selective agonists that bind to all MCRs, although -MSH had a relatively lower affinity for mouse MC1R compared to human (mouse IC 50 = 316  93 nM vs. human IC 50 = 5.97 nM) (Haskell-Luevano et al 1997). Furthermore, we found that neither MC1R, MC3R nor MC5R had a high affinity for LY2112688, whereas MC4R had a high affinity for LY2112688 supporting results found in human (Greenfield et al 2009). PG-901 is in the literature described as a human MC5R agonist, which also functions as an antagonist at human MC3R and MC4R (Grieco et al 2002), which correlates to results obtained on mouse MCRs.…”
Section: Binding Studiessupporting
confidence: 87%
“…The prevalence of hypertension was markedly lower in MC4R-deficient humans compared with control subjects despite severe obesity and its associated metabolic disorders (34). Even after exclusion of patients taking antihypertensive medications, BP, heart rate, and 24-h norepinephrine excretion were significantly lower in MC4R-deficient subjects than in control subjects.…”
Section: Chronic Activation Of the Cns Pomc-mc3/4r Pathway Causes Snsmentioning
confidence: 86%
“…BP levels have been reported significantly lower in MC4R-deficient subjects than in control subjects. 54 Thus, a functional MC4R is essential for the chronic cardiovascular and metabolic actions of leptin. 55 MSHs have important function in feeding, energy metabolism and inflammation.…”
Section: Function Of Hormones Insulinmentioning
confidence: 99%